Analysis of naturally occurring mutations in the human uptake transporter NaCT important for bone and brain development and energy metabolism - Selch, Stefan; Chafai, Anja; Sticht, Heinrich; Birkenfeld, Andreas L.; Fromm, Martin; König, Jörg (Scientific Reports, 2018)
The human uptake transporter NaCT is important for human brain development, brain function and energy metabolism and mediates the uptake of citrate and other intermediates of the tricarboxylic acid cycle from blood into neurons and hepatocytes. Mutations in the SLC13A5 gene encoding NaCT are associated with epileptic encephalopathy. To gain more insights into the transport mechanisms we analyzed the functional consequences of mutations in the SLC13A5 gene on NaCT-mediated transport function. Using HEK293 cells expressing wild-type and eight mutated NaCT proteins, we investigated the mRNA and protein amount as well as the protein localization of all NaCT variants. Furthermore, the impact on NaCT-mediated citrate uptake was measured. In addition, a structural model of the transport pore was generated to rationalize the consequences of the mutations on a structural basis. We demonstrated that all proteins were synthesized with an identical molecular weight as the wild-type transporter but several mutations (NaCTp.G219R, -p.G219E, -p.T227M, -p.L420P and -p.L488P) lead to a complete loss of NaCT-mediated citrate transport. This loss of transport activity can be explained on the basis of the developed structural model. This model may help in the further elucidation of the transport mechanism of this important uptake transporter.
EVALuna2:34652

Comparison of Immature Platelet Count to Established Predictors of Platelet Reactivity During Thienopyridine Therapy - Stratz, Christian; Boemicke, Timo; Younas, Iris; Kittel, Anja; Amann, Michael; Valina, Christian M.; Nuehrenberg, Thomas; Trenk, Dietmar; Neumann, Franz-Josef; Hochholzer, Willibald (Journal of the American College of Cardiology, 2016)
Previous data suggest that reticulated platelets significantly affect antiplatelet response to thienopyridines. It is unknown whether parameters describing reticulated platelets can predict antiplatelet response to thienopyridines.The authors sought to determine the extent to which parameters describing reticulated platelets can predict antiplatelet response to thienopyridine loading compared with established predictors.This study randomized 300 patients undergoing elective coronary stenting to loading with clopidogrel 600 mg, prasugrel 30 mg, or prasugrel 60 mg. Adenosine diphosphate (ADP)-induced platelet reactivity was assessed by impedance aggregometry before loading (intrinsic platelet reactivity) and again on day 1 after loading. Multiple parameters of reticulated platelets were assessed by automated whole blood flow cytometry: absolute immature platelet count (IPC), immature platelet fraction, and highly fluorescent immature platelet fraction.Each parameter of reticulated platelets correlated significantly with ADP-induced platelet reactivity (p < 0.01 for all 3 parameters). In a multivariable model including all 3 parameters, only IPC remained a significant predictor of platelet reactivity (p < 0.001). In models adjusting each of the 3 parameters for known predictors of on-treatment platelet reactivity including cytochrome P450 2C19 (CYP2C19) polymorphisms, age, body mass index, diabetes, and intrinsic platelet reactivity, only IPC prevailed as an independent predictor (p = 0.001). In this model, IPC was the strongest predictor of on-treatment platelet reactivity followed by intrinsic platelet reactivity.IPC is the strongest independent platelet count-derived predictor of antiplatelet response to thienopyridine treatment. Given its easy availability, together with its even stronger association with on-treatment platelet reactivity compared with known predictors, including the CYP2C19*2 polymorphism, IPC may become the preferred predictor of antiplatelet response to thienopyridine treatment. (Impact of Extent of Clopidogrel-Induced Platelet Inhibition During Elective Stent Implantation on Clinical Event Rate-Advanced Loading Strategies [ExcelsiorLOAD]; DRKS00006102).
EVALuna2:8706

Establishment of reference values for the lysine acetylation marker N ɛ-acetyllysine in small volume human plasma samples by a multi-target LC–MS/MS method - Geßner, Arne; Mieth, Maren; Auge, Daniel; Chafai, Anja; Müller, Fabian; Fromm, Martin; Maas, Renke (Amino Acids, 2019)
Cardiovascular disease (CVD) and chronic kidney disease (CKD) constitute substantial burdens for public health. The identification and validation of risk markers for CVD and CKD in epidemiological studies requires frequent adaption of existing analytical methods as well as development of new methods. In this study, an analytical procedure to simultaneously quantify ten endogenous biomarkers for CVD and CKD is described. An easy-to-handle sample preparation requiring only 20 µL of human plasma is followed by liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). The method was successfully validated according to established guidelines meeting required criteria for accuracy, precision, recovery, linearity, selectivity, and limits of quantification. The scalability of the method for application in larger cohorts was assessed using a set of plasma samples from healthy volunteers (n = 391) providing first reference values for the recently established biomarker Nɛ-acetyllysine (Nɛ-AcLys). Other biomarkers analyzed were creatinine, β-aminoisobutyric acid (β-AIB), carnitine, 1-methylnicotinamide (1-MNA), citrulline, symmetric dimethylarginine (SDMA), asymmetric dimethylarginine (ADMA), homoarginine (hArg), and ornithine. All obtained results are within reference values specified elsewhere. Overall, these results demonstrate the suitability of the method for simultaneous quantification of ten endogenous biomarkers for CVD and CKD in plasma samples from larger cohorts and allow validation of Nɛ-AcLys as a biomarker in large cohorts.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Cardiovascular disease; Chronic kidney disease; Human plasma; LC–MS/MS; N

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine - Lueneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M.; Xanthakis, Vanessa; Glazer, Nicole L.; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T.; et al. (Circulation-Cardiovascular Genetics, 2014)
Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers.This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium.These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
EVALuna2:8688

Pharmacodynamic safety of clopidogrel monotherapy in patients under oral anticoagulation with a vitamin K antagonist undergoing coronary stent implantation - Valina, Christian; Bömicke, Timo; Abdelrazek, Sherif; Eltaweel, Sara; Stratz, Christian; Ferenc, Miroslaw; Trenk, Dietmar; Chafai, Anja; Neumann, Franz Josef; Hochholzer, Willibald (Platelets, 2019)
Current guidelines recommend as treatment option in patients on oral anticoagulation (OAC) undergoing percutaneous coronary intervention (PCI) an antiplatelet monotherapy with clopidogrel if there is an increased risk for bleeding. However, retrospective data suggested a potential interaction of clopidogrel and the vitamin K antagonist (VKA) phenprocoumon leading to a diminished antiplatelet effect. This would increase the ischemic risk of patients treated with this combination. Thus, this prospective study sought to evaluate the pharmacodynamic effect of clopidogrel monotherapy in patients on phenprocoumon undergoing PCI and assessed clinical outcomes. This study enrolled 100 patients on aspirin plus clopidogrel (DAPT-cohort, without indication for VKA) and 100 patients on clopidogrel monotherapy plus phenprocoumon (OAC-cohort) undergoing elective PCI. Platelet reactivity was assessed by impedance aggregometry on day 1 following PCI. Ischemic (death, stroke, or myocardial infarction) and bleeding (BARC 2–5) events within 12 months were compared in a propensity score adjusted model. Platelet reactivity was not different in the OAC- and DAPT-cohort (187 [127–242] vs. 167 [126–218] AU×min; p = 0.23). Overall, 17 ischemic and 34 bleeding events were recorded during follow-up. The OAC-cohort showed a nonsignificant trend to an 80% higher incidence for ischemic and bleeding events in unadjusted analyses, which disappeared following adjustment (ischemic events HR 1.07, 95%-CI 0.32–3.59, p = 0.91; bleeding events HR 1.25, 95%-CI 0.46–3.40, p = 0.67). Following PCI, the pharmacodynamic effect of a clopidogrel monotherapy together with phenprocoumon is similar as compared to DAPT without a VKA, and not associated with an increased risk for ischemic events beyond the higher underlying baseline risk.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Antiplatelet response; clopidogrel; coronary stent; oral anticoagulation

Pharmacology and clinical pharmacology of methylarginines used as inhibitors of nitric oxide synthases - Kittel, Anja; Maas, Renke (Current Pharmaceutical Design, 2014)
The methylarginines asymmetric dimethylarginine (ADMA) and monomethylarginine (L-NMMA) are endogenously formed inhibitors of nitric oxide synthases (NOS), which have extensively been investigated as risk markers and used as pharmacological tools to study the L-arginine-nitric oxide (NO) pathway in vitro and in vivo. It is the aim of the present review to summarize the clinical and experimental data on the pharmacological properties that are of relevance when planning and conducting experiments and clinical studies involving methylarginines. Key pharmacodynamic and pharmacokinetic data including IC50 values of ADMA and L-NMMA for NOS isoforms and transport proteins, as well as metabolism by dimethylarginine dimethylaminohydrolases (DDAH1 and DDAH2) and alanine-glyoxylate aminotransferase 2 (AGXT2) are discussed.
EVALuna2:8675

Role of alanine:glyoxylate aminotransferase 2 in metabolism of asymmetric dimethylarginine in the settings of asymmetric dimethylarginine overload and bilateral nephrectomy - Rodionov, Roman N.; Martens-Lobenhoffer, Jens; Brilloff, Silke; Hohenstein, Bernd; Jarzebska, Natalia; Jabs, Normund; Kittel, Anja; Maas, Renke; Weiss, Norbert; Bode-Boeger, Stefanie M. (Nephrology Dialysis Transplantation, 2014)
Asymmetric and symmetric dimethylarginines (ADMA and SDMA) predict complications and mortality in cardiovascular and renal diseases. Alanine:glyoxylate aminotransferase 2 (AGXT2) can metabolize both ADMA and SDMA; however, this metabolic pathway is still poorly understood. The goal of our study was to test the hypothesis that AGXT2 is compensatory upregulated in the settings of ADMA overload and bilateral nephrectomy.ADMA was infused for 3 days using osmotic minipumps in mice. Half of the mice underwent bilateral nephrectomy 24 h before the end of the infusion.Infusion of ADMA caused a 3- to 4-fold increase in plasma and urine ADMA levels and a 2- to 3-fold increase in plasma and urine levels of the ADMA-specific metabolite of AGXT2 ?-keto-?-(N,N-dimethylguanidino)valeric acid (DMGV). Bilateral nephrectomy led to an 4-fold increase of plasma SDMA levels, but did not change plasma ADMA levels. Interestingly, plasma levels of DMGV were elevated 32-fold in the mice, which underwent bilateral nephrectomy. Neither bilateral nephrectomy nor ADMA infusion caused upregulation of AGXT2 expression or activity.Our data demonstrate that short-term elevation of systemic levels of ADMA leads to a dramatic increase of DMGV formation without upregulation of AGXT2 expression or activity, which suggests that AGXT2-mediated pathway of ADMA metabolism is not saturated under normal conditions and may play a major role in the maintenance of ADMA homeostasis in the setting of local or systemic elevation of ADMA levels.
EVALuna2:8689

The prognostic biomarker L-homoarginine is a substrate of the cationic amino acid transporters CAT1, CAT2A and CAT2B - Chafai, Anja; Fromm, Martin; König, Jörg; Maas, Renke (Scientific Reports, 2017)
Low plasma concentration of L-homoarginine is an independent predictor of cardiovascular events and total mortality. Experimental data indicate that supplementation of L-homoarginine may have protective effects. We aimed to elucidate the mechanisms involved in the cellular uptake of L-homoarginine, which are little understood, so far. Using human embryonic kidney (HEK293) cell lines stably overexpressing the human cationic amino acid transporters CAT1 [solute carrier family 7 (SLC7A1)], CAT2A (SLC7A2A) or CAT2B (SLC7A2B) we assessed the transport kinetics of L-homoarginine and interactions with the CAT substrates L-arginine and asymmetric dimethylarginine (ADMA). Significant uptake of L-homoarginine was observed for all three CATs with apparent KM-values of 175 ± 7 µM for CAT1 and 523 ± 35 µM for CAT2B. Saturation of CAT2A-mediated L-homoarginine uptake could not be reached. Uptake of L-homoarginine by any of the three CATs could be inhibited by L-arginine and ADMA. Significant inhibition of CAT1-mediated uptake of L-homoarginine by L-arginine already occurred in the physiological concentration range. Taken together these data demonstrate that L-homoarginine is a substrate of CAT1, CAT2A and CAT2B and that CAT1 is a key site with regard to physiological relevance and interactions with related substrates such as L-arginine.
EVALuna2:32821